Social Situation Kurds in Ibn Hawqal and Al-Maqdisi’s Books: Comparative Critical Study - Sakar Muhammad Saddiq Habib (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The 10th AD century (4th AH) was considered a summit development of the Islamic civilization, one of these developments was the science of countries. At this period, a two person of knowledgeable about countries, (Ibn Ḥawqal) and (al-Maqdisī) were contributed to this development with two samples of most notable books titled (Ṣūrat al-’Arḍ) and (Ahsan Al-taqasim Fi Maʻrifat Al-aqalim), respectively. Additionally, the two books became the reference of obtaining and providing a valuable information about peoples. In the meantime, presenting important information about Kurds. This research will focus on some aspects of social environment, such as Kurds originates, tribes and clans, behavior, religious believes, language, cloths, celebration and ceremony, foods, drinks, strangeness and oddity of Kurds. In this research study the historical approach was used. In addition, it was supported by available books and comparing them with respect presenting information on Kurdish country.